Adaptation of the Ukrainian version of the «Spiritual Health Assessment Scale» (SHAS) - Lazorko , Olha (Psychological Prospects Journal, 2021)
Purpose. The article presents the results of the Ukrainian-language adaptation of the questionnaire «Personal Spiritual Health Assessment Scale», developed in 2014 by K.L. Gaur (Republic of India), designed to measure the state of mental health of the individual. The scale contains three blocks for measuring spiritual health: Self-development, Self-actualization, and Self-realization. Each block contains seven statements relating to these concepts. The primary purpose of this study is the translation, adaptation and standardization of this questionnaire for the Ukrainian sample.Methods. The theoretical analysis made it possible to systematize the modern understanding of spirituality and spiritual health of the individual and analyze the components of this construct in the English version of the questionnaire, indicators of its reliability and validity. The potential for the development of spirituality in the recovery process of patients with various types of physical and mental disorders in clinical practice was considered.The empirical analysis consisted of testing the psychometric properties of the Ukrainian version of the questionnaire. To do this, we performed a procedure of double translation of the text and their expert evaluation, verification of the validity and reliability of the test under psychometric requirements, and standardization of the test on a non-clinical sample.Statistical data processing was performed using factor analysis.Results. The procedure of adaptation of the SHAS questionnaire demonstrated high psychometric properties: indicators of reliability and design validity fully meet the psychometric requirements. The internal consistency index (Cronbach's alpha) is 0.79, the retest reliability index is r = 0.76, p
Keywords: spirituality, spiritual health, self-development, self-actualization, self-realization.